Goal setting: The role of feedback, external incentives, resource availability, and situational constraints on employees’ performance. - Georgila, Thiresia (2017)
Theoretical Background This research examines the process through which a goal oriented environment can impact on individual performance and specifically, it explores factors that are related with goal setting and the way they influence the employees’ performance outcome. The study places emphasis on an unstable and insecure working setting and explores those factors in a country that has been affected by the financial crisis to a large degree. In particular, the present study investigates the relationships among the amount and frequency of feedback that employees receive with their perception about their improvement of performance due to feedback. In addition, the reported research seeks to expand our knowledge on the effect of financial incentives that employees are offered on their performance enhancement. The final factor that this study investigates is the availability of resources and the presence of situational constraints, and their relationship with the promotion of employees’ job performance. The resources and constraints are distinguished into training, autonomy and work overload.